THE USE OF DIGITAL LITERATURE IN TEACHING READING NARRATIVE TEXT - Sumi Handayani; Lilies Youlia; R Bunga Febriani; Syafryadin Syafryadin (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2020)
This study investigated the use of digital literature in teaching reading narrative text in a State High School in Ciamis. This study is aimed to finding out the teachers’ implementation of using digital literature in teaching reading narrative text and the students’ perception of using digital literature in teaching reading narrative text. Therefore, the writer took one English teacher and one class of eleventh grade students as the purposive sampling. Furthermore, the writer used case study as her research design and conducted the classroom observations to find out how the teacher implemented the digital literature in teaching reading narrative text. The questionnaire was used to figuring the students’ perception of using digital literature in teaching reading narrative text. The finding of the study showed that the teacher implemented well of the use digital literature in teaching and learning process. Besides, there were a lots of students influenced of using digital literature in teaching and learning activity. For example, students felt enjoyable and they became more active in the classroom. It can be concluded that the use of digital literature enabled students to comprehend the narrative text easier. Finally, the writer suggests that the English teacher should implement the digital literature on teaching reading of narrative text during the learning process